The sacred violence according to René Girard the scapegoat and the civilising aspect of the sacred - Korusiewicz, Maria (Folia Philosophica, 2000)
In the present article, another of the author's studies on Girard, she analyses the mechanism of the scapegoat (scapegoating), which not only underlies sacrificial rituals, but also provides the foundations of the civilising function of the sacred, making it possible to organise the life of a given community, and to channel the most destructive type of violence and transform it into a factor that strengthens the communal ties. This happens at the cost of a substitutive victim selected on the basis sacrificial signs and stereotypes, that is accusations of having broken a taboo. The aim of the ritual then is not so much to establish a contact with the godhead, but rather to construct and sustain the social life of a given group, particularly if the community in question has not developed an objective legal system that could prevent outbreaks of violence disrupting its integrity. The article concludes with an attempt to systematise René Girard’s views on the basis of the mechanism of the scapegoating in the development of cultural forms.